Cantrang yang Dilarang : Potret Dinamika Protes Nelayan Juwana - Arum Isnaeny Kasanti; Muhammad Adnan (Journal of Politic and Government Studies, 2019)
The policy on prohibiting the use of cantrang contained in ministerial regulation Maritime Affairs and Fisheries number 2 of 2015 is a solution made by the Minister of Maritime Affairs and Fisheries to maintain the sustainability of the marine ecosystem. The emergence of this policy encouraged fishermen protests throughout Indonesia, including in Juwana Pati Regency, Central Java. The protest movement of fishermen rejected the policy of prohibiting the use of cantrang in the regions and at the center from 2015 to 2018. This study aims to explain the factors that encourage the protest movement and the dynamics of the Juwana fishermen protest movement. The method used in this study is decriptive qualitative with data collection techniques throughobservation, in-depth interviews and documentation. The data obtained are then analyzed using the regulation method, which compares the data from interviews, obsevational data and document data.The results showed that the protests of Juwana fishermen were caused by several factors including economic factors, socio-cultural factors, and political factors.In addition, the dynamics of the Juwana fishermen protest movement in rejecting the policy of prohibiting the use of cantrang is very long, ranging from regional protests, central protests, complaints to institutions and meetings with Ministers and the President. The protests of the Juwana fishermen were protests that arose due to fishermen's disappointment with the policy. For this reason, the Ministry of Maritime Affairs and Fisheries must be able to find an effective fishing gear as a substitute for cantrang and continue to approach Juwana fishermen to find out the real problems why fishermen do not want to switch fishing gear. Juwana fishermen can follow the agreement given by the KKP related to not adding cantrang vessels, not increasing vessel tonnage and operating in predetermined Fisheries Management Areas.Keywords: Protest, Fishermen, Cantrang Policy